Full Length Interleukin 33 Aggravates Radiation-Induced Skin Reaction - Kurow, Olga; Frey, Benjamin; Schuster, Louis; Schmitt, Verena; Adam, Susanne; Hahn, Madelaine; Gilchrist, Derek; Mcinnes, Iain B.; Wirtz, Stefan; Gaipl, Udo; Krönke, Gerhard; Schett, Georg; et al. (Frontiers in Immunology, 2017)
The interleukin (IL)-1 family member IL-33 has been described as intracellular alarmin with broad roles in wound healing, skin inflammation but also autoimmunity. Its dichotomy between full length (fl) IL-33 and the mature (m) form of IL-33 and its release by necrosis is still not fully understood. Here, we compare functional consequences of both forms in the skin in vivo, and therefore generated two lines of transgenic mice which selectively overexpress mmIL-33 and flmIL-33 in basal keratinocytes. Transgene mRNA was expressed at high level in skin of both lines but not in organs due to the specific K14 promoter. We could demonstrate that transgenic overexpression of mmIL-33 in murine keratinocytes leads to a spontaneous skin inflammation as opposed to flmIL-33. K14-mmIL-33 mice synthesize and secrete high amounts of mmIL-33 along with massive cutaneous manifestations, like increased epidermis and dermis thickness, infiltration of mast cells in the epidermis and dermis layers and marked hyperkeratosis. Using skin inflammation models such as IL-23 administration, imiquimod treatment, or mechanical irritation did not lead to exacerbated inflammation in the K14-flmIL-33 strain. As radiation induces a strong dermatitis due to apoptosis and necrosis, we determined the effect of fractionated radiation (12 Gy, 4 times). In comparison to wild-type mice, an increase in ear thickness in flmIL-33 transgenic mice was observed 25 days after irradiation. Macroscopic examination showed more severe skin symptoms in irradiated ears compared to controls. In summary, secreted mmIL-33 itself has a potent capacity in skin inflammation whereas fl IL-33 is limited due to its intracellular retention. During tissue damage, fl IL-33 exacerbated radiation-induced skin reaction.
EVALuna2:13432

Gut-to-brain spreading of pathology in synucleinopathies: A focus on molecular signalling mediators - Schmitt, Verena; Masanetz, Rebecca Katharina; Weidenfeller, Martin; Ebbinghaus, Lara Savannah; Süß, Patrick; Rosshart, Stephan Patrick; von Hörsten, Stephan; Zunke, Friederike; Winkler, Jürgen; Xiang, Wei (Behavioural Brain Research, 2023)
Synucleinopathies are a group of neurodegenerative disorders, classically characterized by the accumulation of aggregated alpha synuclein (aSyn) in the central nervous system. Parkinson's disease (PD) and multiple system atrophy (MSA) are the two prominent members of this family. Current treatment options mainly focus on the motor symptoms of these diseases. However, non-motor symptoms, including gastrointestinal (GI) symptoms, have recently gained particular attention, as they are frequently associated with synucleinopathies and often arise before motor symptoms. The gut-origin hypothesis has been proposed based on evidence of an ascending spreading pattern of aggregated aSyn from the gut to the brain, as well as the comorbidity of inflammatory bowel disease and synucleinopathies. Recent advances have shed light on the mechanisms underlying the progression of synucleinopathies along the gut-brain axis. Given the rapidly expanding pace of research in the field, this review presents a summary of the latest findings on the gut-to-brain spreading of pathology and potential pathology-reinforcing mediators in synucleinopathies. Here, we focus on 1) gut-to-brain communication pathways, including neuronal pathways and blood circulation, and 2) potential molecular signalling mediators, including bacterial amyloid proteins, microbiota dysbiosis-induced alterations in gut metabolites, as well as host-derived effectors, including gut-derived peptides and hormones. We highlight the clinical relevance and implications of these molecular mediators and their possible mechanisms in synucleinopathies. Moreover, we discuss their potential as diagnostic markers in distinguishing the subtypes of synucleinopathies and other neurodegenerative diseases, as well as for developing novel individualized therapeutic options for synucleinopathies.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Alpha synuclein; Gut-to-brain communication; Inflammatory bowel disease; Multiple system atrophy; Parkinson's disease

Interleukin-36 receptor mediates the crosstalk between plasma cells and synovial fibroblasts - Schmitt, Verena; Hahn, Madelaine; Kästele, Verena; Wagner, Olga; Wiendl, Maximilian; Derer, Anja; Taddeo, Adriano; Hahne, Stefanie; Radbruch, Andreas; Jäck, Hans-Martin; Schuh, Wolfgang; Mielenz, Dirk; et al. (European Journal of Immunology, 2017)
The IL-1 family member IL-36? has proinflammatory and pathogenic properties in psoriasis. IL-36? binds to the IL-36 receptor leading to nuclear factor kappa B/mitogen activated protein kinase mediated cytokine release. The IL-36R antagonist prevents recruitment of IL-1 receptor accessory protein and therefore IL-36-dependent cell activation. In inflamed human tissue, we previously could show that resident B cells and plasma cells (PC) express IL-36?. Further, fibroblast-like synoviocytes (FLS) produced proinflammatory cytokines upon IL-36?-stimulation. We hypothesize an IL-36-specific crosstalk between B cells/PCs and FLS permitting a proinflammatory B cell niche. Here, we firstly demonstrated that B cell lines and B cells from healthy donors express IL-36? and stimulation increased IL-36? in B cells and primary plasmablasts/PCs. Moreover, FLS respond specifically to IL-36? by proliferation and production of matrix metalloproteinases via p38/HSP27 signaling. Importantly, IL-36R-deficiency abrogated IL-36?-induced production of inflammatory mediators in FLS and changed the intrinsic FLS-phenotype. Using an in vitro co-culture system, we could show that IL-36R-deficient FLS had a limited capacity to support PC survival compared to wild-type FLS. Hence, we demonstrated an IL-36R-dependent crosstalk between B cells/PCs and FLS. Our data support the concept of initiation and maintenance of a proinflammatory niche by B cells in the joints. This article is protected by copyright. All rights reserved.
EVALuna2:13406

Translocation of Distinct Alpha Synuclein Species from the Nucleus to Neuronal Processes during Neuronal Differentiation - Pieger, Katharina; Schmitt, Verena; Gauer, Carina; Gießl, Nadja; Prots, Iryna; Winner, Beate; Winkler, Jürgen; Brandstätter, Johann Helmut; Xiang, Wei (Biomolecules, 2022)
Alpha synuclein (aSyn) and its aggregation are crucial for the neurodegeneration of Parkinson's disease (PD). aSyn was initially described in the nucleus and presynaptic nerve terminals. However, the biology of nuclear aSyn and the link of aSyn between subcellular compartments are less understood. Current knowledge suggests the existence of various aSyn species with distinct structural and biochemical properties. Here, we identified a C-terminal-targeting aSyn antibody (Nu-aSyn-C), which has a high immunoaffinity towards aSyn in the nucleus. Comparing the Nu-aSyn-C antibody to aSyn antibodies developed against phosphorylated or aggregated forms, we observed that nuclear aSyn differs from cytosolic aSyn by an increased phosphorylation and assembly level in proliferating cells. Employing Nu-aSyn-C, we characterized aSyn distribution during neuronal differentiation in midbrain dopaminergic neurons (mDANs) derived from human-induced pluripotent stem cells (hiPSCs) and Lund human mesencephalic cells, and in primary rat hippocampal neurons. We detected a specific translocation pattern of aSyn during neuronal differentiation from the nucleus to the soma and finally to neuronal processes. Interestingly, a remarkable shift of Nu-aSyn-C-positive species towards neurites was detected in hiPSC mDANs from a PD patient carrying aSyn gene duplication. Together, our results reveal distinct nuclear and cytosolic aSyn species that redistribute during neuronal differentiation-a process that is altered in PD-derived neurons.
CRIS-Team WoS Importer:2022-09-09